Rancang Bangun Sistem Informasi Remunerasi Jasa Pelayanan RSUD Kepahiang Bengkulu Menggunakan Metode FAST - Hendryani, Atika (Universitas Diponegoro, 2017)
The good remuneration information system services can provide useful information for hospital administrators to evaluate employee performance. The aim of this research is to develop a remuneration system services to support employee performance evaluation Kepahiang Hospital. System development methods using FAST (Framework for the Application of Systems Thinking) / Framework for Application of Systems Thinking. Evaluation results of employee performance become the basis of government decision-makers to make improvements and reward. Data used in the research is the data of performance of employees and the amount of revenues from services. Remuneration information system services to produce output tables and graphs to support employee performance evaluation in hospitals Kepahiang for various levels of management. The quality of the information system of the proposed system is better than the old information system.